Producción de jabón para manos a partir de aceite de girasol reciclado (2023)
The large amount of waste produced by saturated and supersaturated sunflower oil generates health problems in humans, in addition to triggering problems due to contamination in the environment, either due to poor disposal or poor management. For this reason, the decision is made to use it as raw material for the bar soap production process, where the different purification stages are taken into account so that it is optimal for the desired use in this degree work.